Finance and Development, June 2005. (Finance and Development; Finance and Development ;, 2005)
The paper highlights that over the past century, access to education has increased enormously, illiteracy has fallen dramatically, and a higher proportion of people are completing primary, secondary, or tertiary education than ever before. But huge problems remain. About 115 million children of primary school age are not currently enrolled in school. Most are illiterate and live in absolute poverty-the majority female. Some 264 million children of secondary school age are not currently enrolled, and the quality of schooling is often low.